Penerimaan dan Penggunaan SuperApp BYOND BSI: Ekstensi Teori Technology Acceptance Model - Nur Arbaien, Muhamad Fasya; Nurkaromah, Silvia Ripa; Sutarman, Sinta; Apriyani, Hilda (Masoem University, 2025)
Bank Syariah Indonesia launched SuperApp BYOND by BSI as the successor to the BSI mobile banking app, featuring innovations such as high-level cyber security, easy access to BSI products, and social and spiritual service features. Customer's acceptance and use of this application is still a challenge that needs attention. This research uses a quantitative method with the Technology Acceptance Model theory approach. The objective was to determine the factors that influence BSI customers' acceptance of BYOND SuperApp. The results of this research found that TAM components such as perceived usefulness, perceived convenience, attitudes, intentions, and trust affect the use of the BYOND by BSI mobile banking application by customers. As a result, feature development, security enhancement, and customer education are strategic steps to support the successful implementation of mobile banking technology in Indonesia.